La mécanique des fluides en France dans la première moitié du xxe siècle - Charru, François (Comptes Rendus. Mécanique, 2023)
French fluid mechanicians of the first half of the Twentieth Century, unlike their illustrious predecessors, appear scarcely mentioned in textbooks and reviews. In particular, French contributions to the boundary layer and turbulence theories – major breakthroughs of the period – seem quite modest. However, contemporary PhD theses, journals and correspondence reveal remarkable works undertaken by outstanding personalities. From 1929, a key instigator of these achievements was the Air Ministry, which, with great open-mindedness, created and financed four institutes of fluid mechanics and five teaching centers in faculties of science. This reveals a fruitful interwar period, which prepares the prominent role played by France in the creation in 1946 of the International Union of Theoretical and Applied Mechanics (IUTAM). This paper recounts this story, with attention paid to the connection between scientific questions and social and cultural issues, in a period marked by two world wars and great strengthening of international relationships.